Developing a Bilingual Guidebook for Brawijaya Museum Malang - Lailiatul Maghfirah (Jurnal Linguistik Terapan, 2024)
Museums are suitable places to display historical relics of the past, which are certainly highly appreciated by the local community and tourists. However, not all museums provide information media that can be accessed by all visitors from different language backgrounds. Based on the preliminary study, Brawijaya Museum in Malang still lacks information media that foreign tourists can access. The museum has a guidebook, but it is still an Indonesian version and needs more content, layout, and design improvement. At the same time, they did not have a tour guide who could speak English. Therefore, this study aims to develop a bilingual guidebook for the Brawijaya Museum in Malang. This study applied the Design and Development Research method by Richey and Klein (2014), which includes five stages: analysis, design, development, implementation, and evaluation. The researcher collected the data by interviewing the museum staff, distributing questionnaires, and conducting observations. The questionnaire was distributed to 60 respondents for feedback, and the results were used to improve the quality of the guidebook. Finally, the bilingual guidebook can be used by local and international tourists as a source of information about museum collections.